Impact of oil selection and cooking methods on acrylamide levels in different potato products - Shenaj Skenderoska Adjija; Tanja Petreska Ivanovska; Marija Dimitrovska; Zoran Zhivikj; Lidija Petrushevska-Tozi; Biljana Chuleva (Makedonsko Farmacevtski Bilten, 2025)
This study investigated the effects of frying method and oil type on acrylamide formation in different potato products. Acrylamide levеls were analyzed in three types of potatoes: organic potatoes, pre-treated French fries, and wedge-style potatoes, using an LC-MS/MS method. All samples were cooked using three common methods in Macedonian cusine - air frying, oven baking and pan frying, and using two types of oil, palm oil and sunflower oil. The highest acrylamide content was found in organic potatoes pan-fried in sunflower oil for 10 minutes (924.93 ± 0.66 µg/kg). French fries showed moderate acrylamide levels, while wedges generally had the lowest levels, particularly when pan-fried in palm oil (140.37 ± 0.47 µg/kg) for 5 minutes. The results from statistical correlations between sample type, cooking method, and oil type with acrylamide formation suggest that while cooking method and oil type may have a modest impact on acrylamide formation, the type of potato product plays a more significant role, with an inverse relationship observed. Additionally, due to the lack of standardized and controlled cooking conditions, such as precise temperature and time settings, home-cooked potatoes tend to have higher acrylamide levels compared to French fries prepared in fast-food restaurants. Thus, the current understanding provides adequate basis for future studies that target on improving cooking conditions to lower acrylamide levels in home-prepared foods.